Genetic diversity and population structure analysis of a diverse panel of pea (Pisum sativum) - Brhane, Haftom; Hammenhag, Cecilia (Frontiers in Genetics, 2024)
Breeding resilient cultivars with increased tolerance to environmental stress and enhanced resistance to pests and diseases demands pre-breeding efforts that includes understanding genetic diversity. This study aimed to evaluate genetic adiversity and population structure of 265 pea accessions. Diversity Arrays Technology (DArT) sequencing technologygenotyping method was employed to identify single nucleotide polymorphisms (SNPs) and silico markers. After stringent filtering, 6966 SNP-and 8454 silico markers were selected for diversity analysis. Genetic diversity was estimated by grouping accessions based on plant material type, geographic origin, growth habit, and seed color. Generally, diversity estimations obtained using SNPs were similar to those estimated using silico markers. The polymorphism information content (PIC) of the SNP markers ranged from 0.0 to 0.5, with a quarter of them displaying PIC values exceeding 0.4, making them highly informative. Analysis based on plant material type-based revealed narrow observed heterozygosity (Ho = 0.02-0.03) and expected heterozygosity (He = 0.26 to 0.31), with landrace accessions exhibiting the highest diversity. Geographic origin-based diversity analysis revealed Ho = 0.02-0.03 and He = 0.22 to 0.30, with European accessions showing the greatest diversity. Moreover, private alleles unique to landrace-(4) and European (22) accessions were also identified, which merit further investigation for their potential association with desirable traits. The analysis of molecular variance revealed a highly significant genetic differentiation among accession groups classified based on seed color, growth habit, plant material types, and geographic origin (p < 0.01). Principal coordinate analysis and Neighbor-joining cluster analysis revealed weak clustering of accessions at different grouping level. Recombination of alleles via crossbreeding genetically distinct accessions from different seed colors and growth habits can potentially lead to the development of superior cultivars. This study underscores the significance of genetic diversity in pea collections, offering valuable insights for targeted breeding and conservation efforts. By leveraging genomic data and exploring untapped genetic resources, pea breeding programs can be fortified to ensure sustainable plant protein production and address future challenges in agriculture.